2018
DOI: 10.1101/310714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anthropogenic habitat alteration leads to rapid loss of adaptive variation and restoration potential in wild salmon populations

Abstract: Anthropogenic habitat alterations can drive phenotypic changes in wild populations. However, the underlying mechanism (i.e., phenotypic plasticity and/or genetic evolution) and potential to recover previous phenotypic characteristics are unclear. Here we investigate the change in adult migration characteristics in wild salmon populations caused by dam construction and other anthropogenic habitat modifications. Strikingly, we find that dramatic allele frequency change from strong selection at a single locus exp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 49 publications
1
65
0
2
Order By: Relevance
“…Applying modern genetic techniques to ancient tissue is an emerging and powerful tool for understanding historical contexts for conservation, such as verifying population extinctions (Iwamoto, Myers, & Gustafson, ) or loss in diversity (Thompson et al., ). Our work utilized such genetic tools to build upon previous studies that used century‐old salmon cannery data and reported similar declines for multiple species across the Northeast Pacific (Gresh, Lichatowich, & Schoonmaker, ).…”
Section: Discussionmentioning
confidence: 99%
“…Applying modern genetic techniques to ancient tissue is an emerging and powerful tool for understanding historical contexts for conservation, such as verifying population extinctions (Iwamoto, Myers, & Gustafson, ) or loss in diversity (Thompson et al., ). Our work utilized such genetic tools to build upon previous studies that used century‐old salmon cannery data and reported similar declines for multiple species across the Northeast Pacific (Gresh, Lichatowich, & Schoonmaker, ).…”
Section: Discussionmentioning
confidence: 99%
“…The first step to effectively apply genomics data to conservation is to identify the single gene or multigene combinations that underpin the focal trait of interest. In some cases, single large‐effect genes may underlie important traits (Barson et al, ; Hess, Zendt, Matala, & Narum, ; Narum, Genova, Micheletti, & Maass, ; Pearse, Miller, Abadía‐Cardoso, & Garza, ; Prince et al, ; Thompson et al, ). However, the reigning paradigm in quantitative genetics posits that most complex traits are controlled by many genes of small effect (Bernatchez, ; Lynch & Walsh, ; Pavey et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Though such assessments have progressed toward unraveling complex relationships between fitness‐related traits and underlying genomic architectures in more easily accessible systems (e.g., Pacific salmonids [ Oncorhynchus spp., Salmo spp. ]; Ayllon et al, ; Barson et al, ; Prince et al, ; Thompson et al, ), applications of NGS to large pelagic fishes are just getting started, and recent studies illustrate the utility of genomic methods for resolving spatial patterns of connectivity in pelagic systems. For example, results from early comparisons of traditional markers (e.g., allozymes, mtDNA, microsatellites) in yellowfin tuna ( Thunnus albacares ) from the Atlantic, Pacific, and Indian oceans were either consistent with genetic homogeneity or offered only preliminary evidence for population subdivision (Appleyard, Grewe, Innes, & Ward, ; Dammannagoda, Hurwood, & Mather, ; Díaz‐Jaimes & Uribe‐Alcocer, , ; Ely et al, ; Scoles & Graves, ; Ward, Eiliott, Grewe, Smolenski, & Sea, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%